Integrated Farming System (IFS) - A Way to Maintain the Sustainability and Enhance the Income - Karthik, Rayapati; M. Venkata Ramana; Ch Pragathi Kumari; M Sharath Chandra; M Santosh Kumar (Chronicle of Bioresource Management, 2023)
India’s agriculture production has increased six fold, but, at the cost of degradation of natural resources. The development took place in well-endowed regions and the smallholder farmers are less benefitted. To tackle such problems, farming systems approach has been widely recognized. The integration of mono-crop farms with agroforestry, fisheries and animal husbandry can play a significant role in better utilization of resources, enhancing farm household income and security of the farmers. The integrated farming system (IFS) approach visualizes a change in the farming techniques for maximum productivity by optimal utilization of various resources. It minimizes the risk and provides stable and regular income throughout the year. IFS model enables to absorb CO2 than the emissions which make it climate resilient compared to cropping systems and it reduces the dependence on external resources through efficient recycling of on-farm biomass and other resources.